Biologics and oral systemic treatment preferences in patients and physicians for moderate-to-severe atopic dermatitis: a discrete choice experiment in the United Kingdom and Germany - Nicholas Durno; Pablo Arija; Krystallia Pantiri; Marieke Heisen; Marco Boeri; Josef Paris; Katrin Jack; Olivier Chambenoit; Ramkumar Subramanian; Jorge Puelles; Elly Stolk; Ben van Hout; et al. (Journal of Dermatological Treatment)
Background: As the available treatments for moderate-to-severe atopic dermatitis (AD) expand, understanding patient and physician preferences becomes crucial for informed decision-making.Objective: To quantify patient and physician preferences for biologics and oral systemic AD treatment attributes.Materials and methods: We conducted a cross-sectional, online discrete choice experiment (DCE) involving 306 AD patients and 206 physicians throughout the United Kingdom and Germany. Qualitative interviews identified the key attributes for inclusion in the DCE. Each choice task comprised two hypothetical patient profiles. Data were analyzed using a random-parameters logit model.Results: Results indicated a significant emphasis on efficacy, with reducing sleep disturbance and itch ranking first and second among patients, and the reverse for physicians. Time to itch relief was the third most important efficacy attribute for both groups, but relatively more important for patients than for physicians. For both groups, the risk of eye problems was the most important safety concern of those included. Mode of administration was not of great importance compared to efficacy and safety attributes.Conclusions: Our findings suggest patients prioritize sleep disturbance, an attribute not captured in prior preference studies in AD, time to itch relief and itch. These findings emphasize the importance of addressing sleep-related issues, whilst also targeting fast itch control, to enhance patients’ well-being.